High-impact-resistance light-weight high-strength composite board and preparation method thereof

By adopting a hot press composite process in epoxy glass fiber composite materials, the glass fiber cloth reinforced polyurethane film and polyamide-polyether block copolymer film are combined to form a high-tough surface layer, and the epoxy resin and modified hollow glass microspheres are combined to form a low-density core layer, which solves the problem of insufficient impact resistance of existing composite materials and achieves high impact resistance, lightweight and high-strength composite board preparation.

CN119704715AActive Publication Date: 2025-03-28ZHONGKE WEIHE TECH (ZHAOQING) CO LTD

Patent Information

Application Number
CN202411982291.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing hollow glass microsphere-filled epoxy glass fiber composites lack impact resistance, which limits their application in automobiles, home appliances and 3C electronic products.

Method used

By combining the glass fiber cloth reinforced polyurethane film with the polyamide-polyether block copolymer film to form a high-toughness surface layer, then combining epoxy resin with modified hollow glass microspheres to make a low-density core layer. Finally, the high-toughness surface layer and the low-density core layer are combined through the hot pressing composite process to prepare a high-impact lightweight high-strength composite board.

Benefits of technology

It achieves high impact resistance of composite boards, can withstand large impact forces without easy breakage, and is suitable for automobiles, home appliances and 3C electronic products, while maintaining lightweight and high-strength characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704715A_ABST
    Figure CN119704715A_ABST
Patent Text Reader

Abstract

The invention relates to a high-impact-resistance light-weight high-strength composite board and a preparation method thereof.The preparation method comprises the following steps that S1, a first glass fiber cloth is arranged between two thermoplastic polyurethane films, hot pressing is conducted, and a glass fiber cloth reinforced polyurethane film is obtained; placing the polyamide-polyether block copolymer film between two adjacent layers of glass fabric reinforced polyurethane films, and performing hot pressing to obtain a high-toughness surface layer; s2, adding the modified hollow glass microspheres, bisphenol A epoxy resin, polyurethane modified epoxy resin, dicyandiamide and an accelerant into a solvent to obtain a resin solution; immersing second glass fiber cloth into the resin glue solution, taking out the second glass fiber cloth after the second glass fiber cloth is completely immersed, and baking the second glass fiber cloth to obtain an epoxy glass fiber prepreg; s3, stacking the plurality of epoxy glass fiber prepregs to obtain a low-density core layer; and S4, stacking the low-density core layer between two adjacent high-toughness surface layers, and performing hot pressing to obtain a target product. The high-strength and high-impact-resistance building material has the advantages of light weight, high strength and high impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and more particularly to a high-impact, lightweight and high-strength composite board and a preparation method thereof. Background Art

[0002] As a synthetic foam reinforced with glass fiber cloth, the epoxy glass fiber composite material filled with hollow glass microspheres has a lower density and better static mechanical strength. For example, the ultra-low density epoxy glass fiber composite material prepared in patent CN201410127336 has a density as low as 0.7g / cm 3 , with a bending strength of about 254MPa. Therefore, as a lightweight and high-strength composite material, it is widely used in fields that require both weight reduction and structural strength.

[0003] However, since both thermosetting epoxy resins and hollow glass microspheres are relatively brittle, the toughness and impact resistance of epoxy glass fiber composites filled with a large number of hollow glass microspheres are poor, which limits their application in fields with high requirements for impact resistance, such as automobiles, home appliances, and 3C electronic products. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-impact-resistant, lightweight and high-strength composite board and a preparation method thereof, which has the advantages of light weight, high strength and high impact resistance.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing a high-impact, lightweight and high-strength composite board comprises the following steps: S1, arranging the first glass fiber between two thermoplastic polyurethane films, hot pressing, and obtaining a glass fiber cloth reinforced polyurethane film; Placing a polyamide-polyether block copolymer film between two adjacent layers of the glass fiber cloth reinforced polyurethane film, and hot pressing to obtain a high-toughness surface layer; S2, adding modified hollow glass microspheres, bisphenol A epoxy resin, polyurethane modified epoxy resin, dicyandiamide, and accelerator into the solvent, mixing evenly, and obtaining a resin solution; Dipping the second glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain an epoxy glass fiber prepreg; S3, stacking a plurality of the epoxy glass fiber prepreg sheets to obtain a low-density core layer; S4, stacking the low-density core layer between two adjacent high-toughness surface layers, and hot pressing to obtain the target product.

[0006] In one embodiment, the S2 specifically includes the following steps: S21, dissolving the modified nitrile rubber using butanone to obtain a modified nitrile rubber solution; S22, adding hollow glass microspheres to the modified nitrile rubber solution, soaking, mixing and then filtering out the modified nitrile rubber solution to obtain the modified hollow glass microspheres; S23, adding the bisphenol A epoxy resin, the polyurethane modified epoxy resin, the dicyandiamide, and the accelerator to the solvent, mixing them evenly, to obtain a mixture solution; S24, adding the modified hollow glass microspheres into the mixture solution, mixing evenly, and obtaining the resin glue solution.

[0007] In one embodiment, in S22, the specific steps of soaking are: firstly stirring at a medium speed to evenly disperse the hollow glass microspheres, and then continuing stirring at a low speed for 6-24 hours.

[0008] In one embodiment, the S23 further comprises: using the solvent to pre-dissolve a portion of the bisphenol A epoxy resin, and using ethylene glycol monomethyl ether to pre-dissolve the dicyandiamide and the accelerator.

[0009] In one embodiment, the S3 further includes: performing hot pressing treatment on the low-density core layer.

[0010] In one embodiment, in S4, at least two low-density core layers are provided.

[0011] In one embodiment, the mass fractions of each component in the resin glue are: 50-100 parts of bisphenol A epoxy resin; Polyurethane modified epoxy resin 50-100 parts; Accelerator 0.02-0.5 parts; 5-50 parts of modified nitrile rubber; 170-270 parts of hollow glass microspheres; 2-15 parts of dicyandiamide.

[0012] In one embodiment, the solvent is at least one of butanone and acetone, and the promoter is dimethylimidazole or 2-ethyl-4-methylimidazole.

[0013] A high-impact, lightweight and high-strength composite board is prepared by the above preparation method.

[0014] In one embodiment, the thickness of the high-toughness surface layer is 10%-50% of the thickness of the low-density core layer.

[0015] The above-mentioned high-impact, lightweight and high-strength composite board and its preparation method have the following beneficial effects: First, by combining glass fiber cloth reinforced polyurethane film with polyamide-polyether block copolymer film to form a high-toughness surface layer, then combining epoxy resin with modified hollow glass microspheres to form a low-density core layer, and finally combining the high-toughness surface layer and the low-density core layer through a hot pressing composite process, a high-impact, lightweight, and high-strength composite board is prepared. This composite board not only maintains the characteristics of light weight and high strength, but also has excellent impact resistance, can withstand large impact forces without being easily broken, and is very suitable for use in fields such as automobiles, home appliances, and 3C electronic products that require high material impact resistance; Secondly, the design is flexible. By flexibly adjusting the number of high-toughness surface layers and low-density core layers, as well as the number of epoxy resin glass fiber semi-cured sheets in the low-density core layer, the specific requirements of material thickness and impact resistance in different application scenarios can be met, thereby optimizing the use efficiency and cost-effectiveness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0017] The present invention is described in further detail below in conjunction with the embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail.

[0018] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0019] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0020] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0021] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0022] A method for preparing a high-impact, lightweight, high-strength composite board, such as Figure 1 As shown, the following steps are included: S1, arranging the first glass fiber between two thermoplastic polyurethane films, hot pressing, and obtaining a glass fiber cloth reinforced polyurethane film; The polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film, and hot pressed to obtain a high-toughness surface layer; In this step, the first glass fiber cloth is a plain glass fiber cloth, and the weight of the plain glass fiber cloth is 48-165g / m 2 , preferably a glass fiber cloth with a lower gram weight, so that the thermoplastic polyurethane can completely penetrate the glass fiber cloth under the action of high temperature and high pressure; the thermoplastic polyurethane film is preferably a polyether thermoplastic polyurethane film, which has a more similar chemical composition to the polyamide-polyether block copolymer film, and there are a large number of reactive chemical groups, so that the high-toughness surface layer can be better combined together; the polyamide-polyether block copolymer is a block copolymer composed of a hard segment and a soft segment, wherein the hard segment is mainly composed of a polyamide (PA) segment, which contains repeated amide groups (-CONH-), which can provide mechanical strength and heat resistance to the material, while the soft segment is composed of a polyether segment, which contains repeated ether bonds (-O-), giving the material flexibility and elasticity. It is this unique molecular structure combination of hard segments and soft segments that makes the amide-polyether block copolymer have high strength, heat resistance, and excellent flexibility and elasticity.

[0023] In actual production, the plain glass fiber cloth and two thermoplastic polyurethane films are placed between each other and subjected to high-temperature hot pressing. The hot pressing temperature is 170-210°C, preferably 180-200°C, and the hot pressing pressure is 25-35kg / cm 2, the hot pressing time is 20-60min, so that the thermoplastic polyurethane film melts and completely infiltrates the plain glass fiber cloth to obtain a glass fiber cloth reinforced polyurethane film with a thickness of 0.05-0.25mm. Then stack them according to the structure of "polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film" to obtain a high-toughness surface layer. It can also be stacked according to the same structure and then hot-pressed again at a high temperature of 170-210°C, preferably 180-200°C, and a hot pressing pressure of 5-10kg / cm 2 The hot pressing time is 60-600s, preferably 150-300s, to obtain a high-toughness surface layer.

[0024] S2, adding modified hollow glass microspheres, bisphenol A epoxy resin, polyurethane modified epoxy resin, dicyandiamide, and accelerator into the solvent, mixing evenly, and obtaining a resin solution; The second glass fiber cloth is immersed in the resin glue solution, taken out after being completely soaked, and baked to obtain the epoxy glass fiber prepreg; In this step, the mixture of bisphenol A epoxy resin and polyurethane modified epoxy resin is used to improve the adhesion and heat resistance of the resin glue while maintaining a certain degree of flexibility. The second glass fiber cloth is immersed in the resin glue and baked so that the resin is evenly distributed in the fiber cloth and initially solidified to form an epoxy glass fiber prepreg. This intermediate product provides the necessary structural strength and bonding performance for subsequent lamination.

[0025] Specifically, the second glass fiber cloth is an electronic grade alkali-free glass fiber cloth, and the gram weight of the electronic grade alkali-free glass fiber cloth is 16-105g / m 2 , preferably 48g / m 2 1080 glass fiber cloth. The lower weight of glass fiber cloth can increase the resin content in the prepreg, which helps to reduce the overall density. The hollow glass microspheres are borosilicate hollow glass microspheres with a density of 0.3-0.6g / cm 3 , particle size D50 is 30-75 μm, particle size D90 is 60-120 μm, and the preferred density is 0.38 g / cm 3 The hollow glass microspheres can effectively reduce the overall density of the material while ensuring sufficient compressive strength.

[0026] S3, stacking a plurality of epoxy glass fiber prepreg sheets to obtain a low-density core layer; In actual production, the stacking quantity and stacking specifications of the prepregs can be flexibly designed according to actual needs.

[0027] S4. Stack the low-density core layer between two adjacent high-toughness surface layers, and hot-press to obtain the target product.

[0028] Specifically, the low-density core layer is stacked between two adjacent high-toughness surface layers, and then placed in a mold covered with a release film or coated with a release agent, and molded according to the set temperature and pressure parameters to ensure that the materials are tightly bonded; after the molding is completed, the fully cured composite board is taken out of the mold, placed in a shaping fixture and cooled to room temperature to obtain a high-impact, lightweight, and high-strength composite board. The surface and bottom layers of the obtained composite board are both high-toughness surface layers with high toughness to improve the impact resistance of the composite board.

[0029] In actual production, the hot pressing temperature of S4 is 70-170℃, and the maximum pressure does not exceed 15kg / m 2 , preferably 10kg / m 2 The hot pressing time is 0.5-3h, preferably 1.5-2.5h. By setting the range value in the vacuum press, the hot pressing temperature and hot pressing pressure are gradually increased to ensure that the epoxy glass fiber semi-cured sheet of the low-density core layer is completely cured.

[0030] The present invention combines a glass fiber cloth reinforced polyurethane film with a polyamide-polyether block copolymer film to form a high-toughness surface layer, then combines epoxy resin with modified hollow glass microspheres to form a low-density core layer, and finally combines the high-toughness surface layer and the low-density core layer through a hot pressing composite process to prepare a high-impact light-weight high-strength composite board. This composite board not only maintains the characteristics of light weight and high strength, but also has excellent impact resistance, can withstand large impact forces without being easily broken, and is very suitable for use in fields such as automobiles, home appliances, and 3C electronic products that require high material impact resistance.

[0031] Furthermore, S2 specifically includes the following steps: S21, dissolving the modified nitrile rubber using butanone to obtain a modified nitrile rubber solution; S22, adding hollow glass microspheres to the modified nitrile rubber solution, soaking, mixing evenly, and filtering out the modified nitrile rubber solution to obtain modified hollow glass microspheres; S23, adding bisphenol A epoxy resin, polyurethane modified epoxy resin, dicyandiamide, and accelerator to the solvent, mixing well, and obtaining a mixture solution; S24, adding modified hollow glass microspheres to the mixture solution, mixing evenly, and obtaining a resin glue solution.

[0032] Specifically, the modified nitrile rubber is preferably a carboxyl-terminated modified nitrile rubber. In actual production, the concentration of rubber in the modified nitrile rubber solution is between 5% and 20%, preferably 6% and 12%. If the concentration is too high, the viscosity is too high and it is not suitable for effectively dispersing the hollow glass microspheres. If the concentration is too low, the amount of modified nitrile rubber adsorbed and deposited on the surface of the hollow glass microspheres during the immersion treatment is too small.

[0033] Because the terminal carboxyl groups of nitrile rubber can interact with the surface hydroxyl groups of hollow glass microspheres through hydrogen bonds, the surface of the modified hollow glass microspheres obtained after the immersion treatment can adsorb a layer of nitrile rubber, avoiding collisions between rigid hollow glass microspheres and with rigid thermosetting epoxy resins, thereby improving the toughness and impact resistance of the composite material. Preferably, acid or alkali can also be used to activate the hollow glass microsphere surface to produce more surface silanols, wherein preferred acid, acid can also catalyze the reaction between silanols and the terminal carboxyl groups of modified nitrile rubber in addition to activating the microsphere surface silanols, further increasing the amount of modified nitrile rubber adsorbed and deposited on the surface of hollow glass microspheres. In order to realize the high concentration of hollow glass microspheres and ensure its good dispersibility, the quality of the modified nitrile rubber solution is 1-3.5 times of the quality of the hollow glass microspheres, preferably 1.5-2.5 times.

[0034] Further, in S22, the specific steps of soaking are: firstly, stirring at a medium speed to evenly disperse the hollow glass microspheres, and then continuing stirring at a low speed for 6-24 hours. In actual production, the speed of medium-speed stirring is 200-800 rpm, and the speed of low-speed stirring is 60-100 rpm.

[0035] Furthermore, S23 also includes: using a solvent to pre-dissolve a portion of the bisphenol A epoxy resin, and using ethylene glycol monomethyl ether to pre-dissolve dicyandiamide and an accelerator.

[0036] Specifically, by pre-dissolving bisphenol A epoxy resin, its dissolution efficiency can be improved, and the efficiency of subsequent reactions can be improved; dicyandiamide is a commonly used latent curing agent, but due to its high polarity in chemical structure, its dispersibility and solubility in epoxy resin are poor, so ethylene glycol monomethyl ether is needed to pre-dissolve dicyandiamide, so that dicyandiamide is dispersed more evenly in the resin glue. At the same time, ethylene glycol monomethyl ether can also improve the solubility and dispersibility of the accelerator, thereby improving the efficiency of the curing reaction.

[0037] Furthermore, S3 also includes: hot pressing the low-density core layer, that is, hot pressing the epoxy glass fiber semi-cured sheet constituting the low-density core layer, and then hot pressing and compounding it with the high-toughness surface layer obtained in S1.

[0038] Furthermore, in S4, at least two low-density core layers are provided to improve the overall impact resistance of the composite board.

[0039] Specifically, since polyurethane-modified epoxy resin is used in the preparation of the low-density core layer, and thermoplastic polyurethane film is used in the preparation of the high-toughness surface layer, the two materials have similar chemical compositions and contain a large number of reactive chemical groups, which results in good bonding between the low-density core layer and the high-toughness surface layer. Therefore, the number of high-toughness surface layers and low-density core layers can be set as required, and stratification is not likely to occur.

[0040] The present invention has great design flexibility and can meet the specific requirements of material thickness and impact resistance in different application scenarios by flexibly adjusting the number of high-toughness surface layers and low-density core layers, as well as the number of epoxy resin glass fiber semi-cured sheets in the low-density core layer, thereby optimizing the use efficiency and cost-effectiveness of the material.

[0041] Furthermore, the mass fractions of the components in the resin glue are: 50-100 parts of bisphenol A epoxy resin; 50-100 parts of polyurethane modified epoxy resin; 0.02-0.5 parts of accelerator; 5-50 parts of modified nitrile rubber; 170-270 parts of hollow glass microspheres; and 2-15 parts of dicyandiamide.

[0042] In actual production, in order to improve the dissolution efficiency of bisphenol A epoxy resin, a solvent can be used to pre-dissolve part of the bisphenol A epoxy resin. Each component of the resin glue (except the solvent) is calculated by weight of the non-volatile matter, and by using the solvent, the solid content of the resin glue is controlled to 50-75%, preferably 65%. By accurately controlling the solid content of the resin glue, the viscosity and fluidity of the resin glue are balanced to ensure that it can fully impregnate the glass fiber cloth without being too viscous to cause processing difficulties.

[0043] Further, the solvent is at least one of butanone and acetone. In actual production, the viscosity and fluidity of the resin glue are increased by adding a solvent, which is convenient for the impregnation and curing process.

[0044] Furthermore, the accelerator is dimethylimidazole or 2-ethyl-4-methylimidazole. In actual production, they have high catalytic activity for the curing of epoxy resin and can significantly improve the curing speed and the performance of the cured resin.

[0045] A high-impact, lightweight and high-strength composite board is prepared by the above preparation method.

[0046] Furthermore, the thickness of the high-toughness surface layer is 10%-50% of the thickness of the low-density core layer, which can significantly improve the impact resistance of the composite board while maintaining the overall lightweight. If the high-toughness surface layer thickness is too low, the impact resistance of the composite board will be deviated; if the high-toughness surface layer thickness is too high, the overall density of the composite board will be too high. Example 1

[0047] This embodiment provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, the basis weight is 105g / m 2 The 2116 glass fiber is arranged between two polyether thermoplastic polyurethane films and hot pressed at a temperature of 180°C and a pressure of 30kg / cm 2 , and then taken out after hot pressing for 40 minutes to obtain a glass fiber cloth reinforced polyurethane film; A 0.1 mm thick polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film, and then hot pressed at a temperature of 180 ° C and a pressure of 8 kg / cm 2 , after hot pressing for 250s, it was taken out and cooled to 25°C to obtain a high-toughness surface layer with a thickness of about 1.20mm; S2, using 320 parts of butanone solution to dissolve 40 parts of modified nitrile rubber to obtain a modified nitrile rubber solution; Add 225 parts of hollow glass microspheres to the modified nitrile rubber solution, stir at a speed of 600 rpm to evenly disperse the hollow glass microspheres, and then continue stirring at a speed of 80 rpm for 24 hours to complete the soaking process, and filter out the modified nitrile rubber solution after mixing evenly to obtain modified hollow glass microspheres; Dissolve 6.4 parts of dicyandiamide and 0.09 parts of dimethylimidazole in 150 parts of ethylene glycol monomethyl ether to obtain a premixed solution; Dissolve 70 parts of solid bisphenol A epoxy resin with an epoxy equivalent weight of about 475 g / eq in 115 parts of acetone, then add the premixed solution, 30 parts of liquid bisphenol A epoxy resin with an epoxy equivalent weight of about 185 g / eq, and 70 parts of polyurethane-modified epoxy resin, mix well, and obtain a mixture solution; Adding modified hollow glass microspheres into the mixture solution, mixing evenly, and obtaining a resin glue solution; The basis weight is 48g / m 2 The 1080 glass fiber cloth was immersed in the resin glue solution, taken out after being completely soaked, and baked at 160°C for 4.5 minutes to obtain the epoxy glass fiber prepreg; S3, stacking 25 zero-degree cut epoxy glass fiber prepregs of the same specifications to obtain a low-density core layer with a thickness of about 5.10 mm; S4, stack the low-density core layer obtained in S3 between two high-toughness surface layers and hot press them at a temperature of 160°C and a pressure of 5 kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 150 minutes, it was taken out and transferred to a cold press to be cooled to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0048] The composite structure of this embodiment is: "high-toughness surface layer-low-density core layer-high-toughness surface layer" arranged from bottom to top, wherein the high-toughness surface layer is composed of 4 glass fiber cloth reinforced polyurethane films and 3 polyamide-polyether block copolymer films stacked alternately, and the upper and lower surfaces of the high-toughness surface layer are both glass fiber cloth reinforced polyurethane films, and the low-density core layer is 25 semi-cured sheets that have not been hot-pressed. Example 2

[0049] This embodiment provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, the basis weight is 78g / m 2 The 2113 glass fiber is arranged between two polyether thermoplastic polyurethane films and hot pressed at a temperature of 180°C and a pressure of 30kg / cm 2 , and then taken out after hot pressing for 40 minutes to obtain a glass fiber cloth reinforced polyurethane film; A 0.125 mm thick polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film, and then hot pressed at a temperature of 180 ° C and a pressure of 8 kg / cm 2 , after hot pressing for 250s, it was taken out and cooled to 25°C to obtain a high-toughness surface layer with a thickness of about 1.20mm; S2, using 300 parts of butanone solution to dissolve 30 parts of modified nitrile rubber to obtain a modified nitrile rubber solution; 235 parts of hollow glass microspheres were added to the modified nitrile rubber solution, and the hollow glass microspheres were evenly dispersed by stirring at a speed of 600 rpm, and then the stirring was continued at a speed of 80 rpm for 24 hours to complete the soaking process, and the modified nitrile rubber solution was filtered out after mixing evenly to obtain modified hollow glass microspheres; Dissolve 7.2 parts of dicyandiamide and 0.12 parts of dimethylimidazole in 150 parts of ethylene glycol monomethyl ether to obtain a premixed solution; Dissolve 60 parts of solid bisphenol A epoxy resin with an epoxy equivalent weight of about 475 g / eq in 130 parts of acetone, then add the premixed solution, 40 parts of liquid bisphenol A epoxy resin with an epoxy equivalent weight of about 185 g / eq, and 80 parts of polyurethane-modified epoxy resin, mix well, and obtain a mixture solution; Adding modified hollow glass microspheres into the mixture solution, mixing evenly, and obtaining a resin glue solution; The basis weight is 48g / m 2 The 1080 glass fiber cloth was immersed in the resin glue solution, taken out after being completely soaked, and baked at 160°C for 4.5 minutes to obtain the epoxy glass fiber prepreg; S3, stack 25 zero-degree cut epoxy glass fiber prepregs of the same specifications to obtain a low-density core layer with a thickness of about 5.10 mm, and perform hot pressing on the low-density core layer at a temperature of 160°C and a pressure of 5 kg / cm 2 Stepwise pressurization up to 10kg / cm 2 , hot pressing for 60min; S4: stack the low-density core layer after the pressure treatment in S3 between two layers of high-toughness surface layers, and hot press at a temperature of 160°C and a pressure of 5kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 150 minutes, it was taken out and transferred to a cold press to be cooled to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0050] The composite structure of this embodiment is: "high-toughness surface layer-low-density core layer-high-toughness surface layer" arranged from bottom to top, wherein the high-toughness surface layer is composed of 4 glass fiber cloth reinforced polyurethane films and 3 polyamide-polyether block copolymer films stacked alternately, and the upper and lower surfaces of the high-toughness surface layer are both glass fiber cloth reinforced polyurethane films, and the low-density core layer is 25 semi-cured sheets that have been heat-pressed. Example 3

[0051] This embodiment provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, the basis weight is 105g / m 2 The 2116 glass fiber is arranged between two polyether thermoplastic polyurethane films and hot pressed at a temperature of 180°C and a pressure of 30kg / cm 2 , and then taken out after hot pressing for 40 minutes to obtain a glass fiber cloth reinforced polyurethane film; A 0.30 mm thick polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film, and then hot pressed at a temperature of 180 ° C and a pressure of 8 kg / cm 2 , after hot pressing for 250s, it was taken out and cooled to 25°C to obtain a high-toughness surface layer with a thickness of about 1.20mm; S2, using 300 parts of butanone solution to dissolve 20 parts of modified nitrile rubber to obtain a modified nitrile rubber solution; Add 245 parts of hollow glass microspheres to the modified nitrile rubber solution, first stir at a speed of 600 rpm to evenly disperse the hollow glass microspheres, then continue stirring at a speed of 80 rpm for 24 hours to complete the soaking process, and filter out the modified nitrile rubber solution after mixing evenly to obtain modified hollow glass microspheres; Dissolve 8.1 parts of dicyandiamide and 0.15 parts of dimethylimidazole in 150 parts of ethylene glycol monomethyl ether to obtain a premixed solution; Dissolve 50 parts of solid bisphenol A epoxy resin with an epoxy equivalent weight of about 475 g / eq in 145 parts of acetone, then add the premixed solution, 50 parts of liquid bisphenol A epoxy resin with an epoxy equivalent weight of about 185 g / eq, and 90 parts of polyurethane-modified epoxy resin, mix well, and obtain a mixture solution; Adding modified hollow glass microspheres into the mixture solution, mixing evenly, and obtaining a resin glue solution; The basis weight is 48g / m 2 The 1080 glass fiber cloth was immersed in the resin glue solution, taken out after being completely soaked, and baked at 160°C for 4.5 minutes to obtain the epoxy glass fiber prepreg; S3, stacking 25 zero-degree cut epoxy glass fiber prepregs of the same specifications to obtain a low-density core layer with a thickness of about 5.10 mm; S4, stack the low-density core layer obtained in S3 between two high-toughness surface layers, and hot press at a temperature of 160°C and a pressure of 5 kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 150 minutes, it was taken out and transferred to a cold press to be cooled to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0052] The composite structure of this embodiment is: "high-toughness surface layer-low-density core layer-high-toughness surface layer" arranged from bottom to top, wherein the high-toughness surface layer is composed of 3 glass fiber cloth reinforced polyurethane films and 2 polyamide-polyether block copolymer films stacked alternately, and the upper and lower surfaces of the high-toughness surface layer are both glass fiber cloth reinforced polyurethane films, and the low-density core layer is 25 semi-cured sheets that have not been hot-pressed. Example 4

[0053] This embodiment provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, the basis weight is 105g / m 2 The 2116 glass fiber is arranged between two polyether thermoplastic polyurethane films and hot pressed at a temperature of 180°C and a pressure of 30kg / cm 2 , and then taken out after hot pressing for 40 minutes to obtain a glass fiber cloth reinforced polyurethane film; A 0.1 mm thick polyamide-polyether block copolymer film is placed between two adjacent layers of glass fiber cloth reinforced polyurethane film, and then hot pressed at a temperature of 180 ° C and a pressure of 8 kg / cm 2 , after hot pressing for 250s, it was taken out and cooled to 25°C to obtain a high-toughness surface layer with a thickness of about 0.84mm; S2, taking the epoxy glass fiber prepreg obtained in S2 of Example 1; S3, stacking 12 zero-degree cut epoxy glass fiber prepregs of the same specifications to obtain a low-density core layer with a thickness of about 2.50 mm; S4, alternately stacking the low-density core layer and the low-density secondary core layer obtained in S3, and then hot pressing, the hot pressing temperature is 160°C, the hot pressing pressure is 5kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 150 minutes, it was taken out and transferred to a cold press to be cooled to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0054] The composite structure of this embodiment is: "high-toughness surface layer-low-density core layer-high-toughness surface layer-low-density core layer-high-toughness surface layer" arranged from bottom to top, wherein the high-toughness surface layer is composed of 3 glass fiber cloth reinforced polyurethane films and 2 polyamide-polyether block copolymer films stacked alternately, and the upper and lower surfaces of the high-toughness surface layer are both glass fiber cloth reinforced polyurethane films, and the low-density core layer is 12 semi-cured sheets that have not been hot-pressed.

[0055] Comparative Example 1 This comparative example provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, the basis weight is 105g / m 2 The 2116 glass fiber is arranged between two thermoplastic polyurethane films with a thickness of 0.1 mm and hot pressed at a temperature of 180°C and a pressure of 30 kg / cm 2 , and then taken out after hot pressing for 40 minutes to obtain a glass fiber cloth reinforced polyurethane film; Five glass fiber cloth reinforced polyurethane films were stacked and hot pressed at a temperature of 180°C and a pressure of 8kg / cm 2 , after hot pressing for 250s, take it out and cool it to 25°C to obtain a high-toughness surface layer with a thickness of about 1.14-1.26mm; S2, take the low-density core layer obtained in S3 of Example 1, and stack it between two layers of high-toughness surface layers, hot press, the hot pressing temperature is 160 ° C, the hot pressing pressure is 5kg / cm 2 Stepwise pressurization up to 10kg / cm 2 After hot pressing for 150 minutes, it was taken out and transferred to a cold press to be cooled to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0056] Comparative Example 2 This comparative example provides a high-impact, lightweight, high-strength composite board, the specific preparation steps of which are: S1, using 66 parts of ethylene glycol monomethyl ether to dissolve 3.4 parts of dicyandiamide and 0.06 parts of 2-methylimidazole to obtain a premixed solution; 65 parts of bisphenol A epoxy resin with an epoxy equivalent of 475 g / eq and 35 parts of bisphenol A epoxy resin with an epoxy equivalent of 185 g / eq were added to 37 parts of acetone, and stirred and dispersed uniformly to obtain a mixture solution; The premixed solution was added to the mixture solution and stirred evenly, and then 78.5 parts of hollow glass microspheres were added to the mixture and stirred evenly to obtain a resin glue solution; The basis weight is 48g / m 2 The 1080 glass fiber cloth is immersed in the resin glue solution, taken out after being completely soaked, and then placed in a 150°C oven for baking for 3.5 minutes to obtain an epoxy glass fiber prepreg. S2. 25 epoxy glass fiber semi-cured sheets are stacked, and a release film is provided on each of the upper and lower surfaces, and then a mirror template is overlapped on both sides to obtain a low-density core layer with a thickness of about 5.10 mm.

[0057] S3, take the high-toughness surface layer obtained in S1 of Example 1, stack the low-density core layer obtained in S2 between the two high-toughness surface layers, send them into a vacuum hot press, and press them at a pressure of 25Kg / cm 2 , temperature 180°C, take out after hot pressing for 60 minutes, transfer to a cold press and cool to 25°C to obtain a target product with a thickness of about 7.50 mm.

[0058] The relevant performance tests were carried out on each embodiment and comparative example, and the results are as follows: Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Impact resistance (drop weight impact test) OK OK OK OK NG NG <![CDATA[Average density (g / cm 3 )]]> 0.94 0.92 0.90 0.94 0.95 0.95 Table 1 Table 1 records the impact resistance and average density of each example and comparative example.

[0059] Examples 1, 2, 3 and 4 all use polyether thermoplastic polyurethane, polyamide-polyether block copolymer, bisphenol A epoxy resin, polyurethane modified epoxy resin and hollow glass microspheres. The results show that the obtained composite panels have excellent impact resistance and can withstand an impact force of more than 400J, which is very suitable for use in fields such as automobiles, home appliances and 3C electronic products that require high material impact resistance.

[0060] Among them, Comparative Example 1 did not use polyamide-polyether block copolymer in the high-toughness surface layer, so the impact resistance was worse than that of Example 1, specifically, the impact dent depth exceeded 3 mm, but there was no interlayer delamination phenomenon; Comparative Example 2 replaced the high-toughness low-density core layer with an ordinary ultra-low-density epoxy glass fiber board filled with hollow glass microspheres on the basis of Example 1, and its impact resistance was worse than that of Comparative Example 1. After the drop hammer impact test, the low-density core layer was penetrated and interlayer delamination problems occurred.

[0061] If the materials mentioned in the above embodiments and comparative examples are in liquid form, they need to be stirred and dispersed evenly; if they are solid, they need to be stirred until they are completely dissolved to avoid affecting the preparation of the target product due to insufficient dissolution.

[0062] The materials used in the above embodiments are as follows: Polyether thermoplastic polyurethane film: Model XG2285 produced by Shanghai Xingeng Environmental Protection Technology Co., Ltd.; Polyamide-polyether block copolymer film: Pebax 2533 produced by Arkema; Modified nitrile rubber: NANCAR 1072CGL model produced by Zhenjiang Nandi Chemical Co., Ltd.; Hollow glass microspheres: H38 model produced by Zhongke Yali Technology Co., Ltd. Bisphenol A epoxy resin: NPES-901 or NPEL-128 produced by Nan Ya Plastics Corporation; Polyurethane modified epoxy resin: EPU-133 model produced by Luohe High-tech Materials (Shanghai) Co., Ltd.

[0063] Relevant performance tests were conducted on the above-mentioned embodiments and comparative examples. Among them, the impact resistance test method of the composite plate is as follows: the sample is fixed on a rigid support, and a drop hammer impact test is performed using a spherical punch with a diameter of 25 mm. The drop weight is 26.5 kg, the drop height is 1558 mm, and the impact potential energy is 400 J. During the test, the sample must withstand the impact loading of a hemispherical punch with a circular convex head. The damage resistance of the sample is determined by the size and form of the impact scar left on the sample. After the drop hammer impact test, the sample is not penetrated, and the impact dent depth is ≤3 mm, which is considered to be passed.

[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high-impact, lightweight, high-strength composite board, characterized in that: The following steps are involved: S1, arranging the first glass fiber between two thermoplastic polyurethane films, hot pressing, and obtaining a glass fiber cloth reinforced polyurethane film; Placing a polyamide-polyether block copolymer film between two adjacent layers of the glass fiber cloth reinforced polyurethane film, and hot pressing to obtain a high-toughness surface layer; S2, adding modified hollow glass microspheres, bisphenol A epoxy resin, polyurethane modified epoxy resin, dicyandiamide, and accelerator into the solvent, mixing evenly, and obtaining a resin solution; Dipping the second glass fiber cloth into the resin glue solution, taking it out after it is completely soaked, and baking it to obtain an epoxy glass fiber prepreg; S3, stacking a plurality of the epoxy glass fiber prepreg sheets to obtain a low-density core layer; S4, stacking the low-density core layer between two adjacent high-toughness surface layers, and hot pressing to obtain the target product.

2. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 1, characterized in that: The S2 specifically includes the following steps: S21, dissolving the modified nitrile rubber using butanone to obtain a modified nitrile rubber solution; S22, adding hollow glass microspheres to the modified nitrile rubber solution, soaking, mixing and then filtering out the modified nitrile rubber solution to obtain the modified hollow glass microspheres; S23, adding the bisphenol A epoxy resin, the polyurethane modified epoxy resin, the dicyandiamide, and the accelerator to the solvent, mixing them evenly, to obtain a mixture solution; S24, adding the modified hollow glass microspheres into the mixture solution, mixing evenly, and obtaining the resin glue solution.

3. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 2, characterized in that: In S22, the specific steps of soaking are: firstly stirring at a medium speed to evenly disperse the hollow glass microspheres, and then continuing stirring at a low speed for 6-24 hours.

4. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 2, characterized in that: The S23 further includes: using the solvent to pre-dissolve a portion of the bisphenol A epoxy resin, and using ethylene glycol monomethyl ether to pre-dissolve the dicyandiamide and the accelerator.

5. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 1, characterized in that: The S3 further includes: performing a hot pressing process on the low-density core layer.

6. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 1, characterized in that: In S4, at least two low-density core layers are provided.

7. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 1, characterized in that: The mass fractions of each component in the resin glue are: 50-100 parts of bisphenol A epoxy resin; Polyurethane modified epoxy resin 50-100 parts; Accelerator 0.02-0.5 parts; 5-50 parts of modified nitrile rubber; 170-270 parts of hollow glass microspheres; 2-15 parts of dicyandiamide.

8. The method for preparing a high-impact, lightweight, high-strength composite board according to claim 1, characterized in that: The solvent is at least one of butanone and acetone, and the accelerator is dimethylimidazole or 2-ethyl-4-methylimidazole.

9. A high-impact, lightweight, high-strength composite panel, characterized in that: The high-impact, lightweight and high-strength composite board is prepared according to the preparation method of any one of claims 1 to 8.

10. The high-impact, lightweight, high-strength composite panel according to claim 9, characterized in that: The thickness of the high-toughness surface layer is 10%-50% of the thickness of the low-density core layer.

Citation Information

Patent Citations

  • Ultralow-density composite material and resin combination prepreg as well as preparation method and applications thereof

    CN103881307A

  • Sandwich composite board and preparation methods thereof

    CN111844996A

  • Preparation method of multi-scale interface toughened resin-based composite material structure

    CN115816922A

  • Flexible photovoltaic backboard and manufacturing method thereof

    CN118248787A

  • Composite Foam Article

    US20220032577A1

Cited By

  • Preparation process and equipment of high-transparency epoxy glass fiber plate

    CN120902319A

  • Process for preparing an epoxy glass fiber board with high transparency and equipment thereof

    CN120902319B